Application of system theoretic accident model and processes (STAMP) in healthcare settings: a scoping review - Zamberi, Bisyarah; Taib, Ibrahim Adham (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2024)
The healthcare industry has seen a rise in adverse events and system failures, highlighting the need for comprehensive safety analysis methods. The System Theoretic Accident Model and Processes (STAMP) offers a systems-based approach to understanding and mitigating complex interactions leading to failures. Despite its application in various industries, there is a gap in the literature regarding the extent of its use in healthcare, including its benefits and limitations. This scoping review investigates the application of STAMP in various medical departments, using the PRISMA-ScR methodology, to identify relevant studies in Scopus, PubMed, and ScienceDirect databases. Nine studies from radiology, cardiology, and other departments were identified, they reported the benefits of using STAMP, such as its ability to uncover system flaws and suggest improvements beyond traditional root-cause methods. They also highlighted several disadvantages, including potential biases and limited level of detail about specific failures. The findings offer valuable insights for researchers and healthcare professionals, indicating that STAMP is a valuable tool for enhancing patient safety and system reliability